Theoretical and Practical Phonetic Instruction in the Eyes of Advanced Students. An Editorial to RiL Special Issue Vol. 21.3 and 21.4 on Pronunciation Research and Pronunciation Learning/Teaching in a Global EFL Perspective - Anna Jarosz (Research in Language)
The article focuses on advanced students’ beliefs and views related to their own pronunciation and pronunciation learning/teaching. It also presents their opinions on the university courses dedicated to phonetics and phonology of the English language. Furthermore, it analyses the students plans and ambitions for their future self-study and intentions to further develop and improve their English pronunciation. Finally, the article introduces varied and numerous research areas investigated in the current two issues of RiL and points to the significance of the most recent findings in the field.